Factorial design of reactive concrete powder containing electric arc slag furnace and recycled glass powder - Abellán-García, Joaquín; Núñez López, Andrés Mauricio; Torres Castellanos, Nancy; Fernández Gómez, Jaime (Universidad Nacional de Colombia, 2020)
The main objective of this research is to develop an optimized mixture of reactive powder concrete (RPC) containing supplementary cementitious materials (SCM), such as Electric Arc Slag Furnace (EASF), and Recycled Glass Powder (RGP) among others, through a factorial design. Accurate polynomial regressions were adjusted between considered factors and obtained responses such spread flow and compressive strength at different ages of the concrete. A multi-objective algorithm was executed to reach an eco-friendly mixture with the proper flow, the highest compressive strength, while simultaneously having the minimum content of cement. The experimental verification of this mathematical optimization demonstrated that the use of 621 kg/m3 of ASTM Type HE cement, with a maximum content of 100 kg/m3 of silica fume, should be considered the most appropriate amount to be employed in the RCP mixture to achieve a value of compressive strength over 150 MPa and a self-compacting mixture.

El objetivo principal de esta investigación es desarrollar una mezcla optimizada de concreto de polvos reactivos (RPC) que contenga materiales cementícios suplementarios (SCM), como la escoria siderúrgica de arco eléctrico (EASF) y el polvo de vidrio reciclado (RGP) entre otros, utilizando el diseño factorial. Se calcularon diferentes regresiones polinómicas para predecir con precisión las variables respuesta (flujo estático y resistencia a compresión a distintas edades) en función de los factores considerados. A través de un algoritmo multiobjetivo, se determinó la mezcla que alcance la resistencia y flujo estático adecuados con un contenido mínimo de cemento. La verificación experimental de esta optimización matemática mostró que con 621 kg/m3 de cemento ASTM Tipo HE, y un contenido máximo de 100 kg/m3 de humo de sílice, se puede alcanzar una resistencia a compresión superior a los 150 MPa en un concreto, además, autocompactante.
Diseño factorial de concretos de polvos reactivos conteniendo escoria de arco eléctrico y polvo de vidrio reciclado
Keywords: RPC; Sustainability; EASF; RGP; Compressive strength; RSM; Optimization; RPC; Sostenibilidad; EASF; RGP; Resistencia a compresión; RSM; Optimización